Drug safety evaluation of aripiprazole in bipolar disorder. Issue 6 (3rd June 2019) - Cuomo, Alessandro; Beccarini Crescenzi, Bruno; Goracci, Arianna; Bolognesi, Simone; Giordano, Nicola; Rossi, Rodolfo; Facchi, Edvige; Neal, Stephen M; Fagiolini, Andrea
ABSTRACT: Introduction : Safety and tolerability of medications are key variables to inform treatment choice for patients with bipolar disorder (BD). This review focuses on the overall tolerability and safety profile of aripiprazole when used for its bipolar disorder indications, which include acute treatment of manic and mixed episodes and maintenance treatment of bipolar I disorder for the oral formulation, agitation associated with bipolar mania for the injectable immediate-release formulation, and maintenance treatment of bipolar I disorder for the long acting once-monthly (AOM) formulation. Areas covered : The authors reviewed aripiprazole safety in bipolar disorder according to product labeling. English language reports located through PubMed and information available on the US Food and Drug Administration (FDA) and European Medicines Agency (EMA) websites, with a focus on the safety and tolerability of aripiprazole, were reviewed. Expert opinion : Compared to many other antipsychotics, aripiprazole has a relatively favorable tolerability profile, with a lower risk for weight gain, dyslipidemia, diabetes, and hyperprolactinemia. Compared to first-generation antipsychotics, and similar to most second-generation antipsychotics, aripiprazole has a reduced propensity for extrapyramidal side effects and a better cardiovascular safety.